Brain metastases in EGFR-positive non-small cell lung cancer: the way to the sanctuary becomes less winding - Passaro, Antonio; Gianoncelli, Letizia; Stati, Valeria; de Marinis, Filippo (Annals of Translational Medicine, 2019)
In every day clinical practice, we find ourselves having to face the age-old problem of brain metastases (BM) in non-small cell lung cancer (NSCLC) patients. Despite the high incidence of cerebral metastasis, either at diagnosis or at relapse/progression, not many treatment options were available beyond radiotherapy for the management of these patients, regardless of EGFR mutational status. Furthermore, NSCLC patients with BM were historically excluded from clinical trials due to their poor prognosis, also related to the reduced intra cerebral drug availability caused by the mechanism of efflux pumps in the blood-brain-barrier (BBB) that contribute to create a pharmacological sanctuary (1,2).